2008
DOI: 10.2478/s11536-008-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of mild atopic dermatitis in adults with probiotics and emollients

Abstract: AbstractAtopic dermatitis is characterized by impaired skin and mucous membrane barrier function. Measures improving barrier integrity decrease the influence of environmental factors that might exacerbate inflammation. Ten adult patients with mild-to-moderate atopic dermatitis consumed for three months fermented with potent antioxidative probiotic, L. fermentum ME-3 (DSM 14241) goat milk 200 mg/day. A control group consisted of six patients, not supplemented by probiotic. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Recent data suggest that an increased production of atherogenic and inflammatory oxLDL within the vessel wall suppresses several immunity-related cells, including regulatory T cells [27] which normally exert antiatherogenic and anti allergic effects. It should be noted that previous trials have shown the positive effect of ME-3 on blood LDL, prolonging its resistance to oxidation, lowering the content of oxLDL and BDC-LDL and enhancing the total antioxidative capacity of the blood [1,11,14]. The systemic influence of LfME-3 on the host´s OxS-load is seen in the decline of the values of isoprostanes, which are accepted as an informative marker for the body's systemic OxS-burden [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that an increased production of atherogenic and inflammatory oxLDL within the vessel wall suppresses several immunity-related cells, including regulatory T cells [27] which normally exert antiatherogenic and anti allergic effects. It should be noted that previous trials have shown the positive effect of ME-3 on blood LDL, prolonging its resistance to oxidation, lowering the content of oxLDL and BDC-LDL and enhancing the total antioxidative capacity of the blood [1,11,14]. The systemic influence of LfME-3 on the host´s OxS-load is seen in the decline of the values of isoprostanes, which are accepted as an informative marker for the body's systemic OxS-burden [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is of human origin [9] and a safety-proven probiotic exhibiting both antimicrobial and antioxidative benefits under different in vitro and in vivo conditions [10][11][12] and having a history of safe use in foodstuffs, especially in kefir, in Finland and the Baltic countries. Encouraged by the results of our previous trials with LfME-3 [1,2,10,11,[13][14][15][16] we aimed to carry out a study to evaluate the effects of kefir enriched with probiotic L. fermentum ME-3 on postprandial oxidative stress, postprandial lipemic response and blood lipoprotein status when added to an ordinary diet.…”
Section: Introductionmentioning
confidence: 99%
“…A food containing an antioxidant LAB strain that has been proven to contain glutathione and has the ability to synthesize and handle glutathione [10] has shown clinically relevant positive effects in humans [4,18]. Now we are able to prove with MALDI-TOF mass spectrometry analysis that the concentration of glutathione in the Figure 3.…”
Section: Discussionmentioning
confidence: 94%
“…There is also support from RCTs for the efficacy of a probiotic mix in patients with inflammatory bowel disease (Kajander et al, 2007;Hovyeda et al, 2009). Nevertheless the evidence to date suggests that the major clinical effects of probiotics are seen in prevention GI disorders, probiotic therapy has also been explored in non-GI diseases, including the treatment of atopic eczema in children and adults (Kalliomaki et al, 2001(Kalliomaki et al, , 2007Kaur et al, 2008). A specialprobiotic, LfME-3, offers a good potential also in cardiovascular health management.…”
Section: Special Clinical Trial With Lactobacillus Strains Concerningmentioning
confidence: 99%